2018
DOI: 10.1177/0741932517749940
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Summarizing and Main Idea Interventions for Struggling Readers in Grades 3 Through 12: 1978–2016

Abstract: This systematic review examines the effects of summarizing and main idea interventions on the reading comprehension outcomes of struggling readers in Grades 3 through 12. A comprehensive search identified 30 studies published in peer-reviewed journals between 1978 and 2016. Studies included struggling reader participants in Grades 3 through 12; targeted summarizing or main idea instruction; used an experimental, quasi-experimental, or single-case design; and included a reading comprehension outcome. A meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 55 publications
1
58
0
2
Order By: Relevance
“…Before beginning the think-aloud, teachers read the text aloud once to students, discuss any unknown vocabulary words and textual features (e.g., charts, graphs, images), and have students state the main idea of the text (cf. Stevens, Park, & Vaughn, 2018). Then, teachers review two common types of purposes for informational texts (persuade, inform).…”
Section: Text Structure Instruction With Authentic Textsmentioning
confidence: 99%
“…Before beginning the think-aloud, teachers read the text aloud once to students, discuss any unknown vocabulary words and textual features (e.g., charts, graphs, images), and have students state the main idea of the text (cf. Stevens, Park, & Vaughn, 2018). Then, teachers review two common types of purposes for informational texts (persuade, inform).…”
Section: Text Structure Instruction With Authentic Textsmentioning
confidence: 99%
“…Main idea abstraction refers to an ability to abstract the mental message from the given test, which is the ultimate goal of reading comprehension. The main idea has a close relationship with reading performance, which in turn determines the reading process (e.g., reading speed) and how the readers can abstract/select the proper reading strategies from their knowledge bases (Hebert et al, 2018; Stevens et al, 2019). Previous studies confirmed that main idea abstraction is a key factor of executive function in reading comprehension.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, if the focus of instruction is mathematics problem solving, a learning strategy specific to mathematics problem solving would be taught within the six stages of SRSD instruction along with self-regulation strategies of goal setting, self-monitoring, self-instruction, and self-reinforcement (see Table 1). The SRSD framework provides a structure for teaching learning and self-regulation strategies that may be applied across content areas, grade levels, and student abilities (Baker et al., 2009; Cuenca-Carlino et al., 2016; Stevens et al., 2019).…”
Section: What Is Srsd?mentioning
confidence: 99%
“…In addition to writing, SRSD is also effective for teaching reading skills to students with SLD. Specific reading strategies taught within the SRSD framework include identification of main idea and details, paraphrasing, and summarizing expository and narrative texts (Stevens et al., 2019). Teaching main idea identification and summarization is effective for students with reading difficulties in upper-elementary grades, middle school, and high school (Stevens et al., 2019) and helps students remember essential information from text they have read (Hagaman & Casey, 2016).…”
Section: Srsd For Readingmentioning
confidence: 99%
See 1 more Smart Citation